The Role of Vitamin C, Vitamin E and Zinc Supplementation in Enhancing the Resilience of Cultured Fish to Environmental Stress: A Systematic Literature Review - Permatasari, Sheny (Open Global Scientific Journal, 2025)
Background: The modern aquaculture industry faces serious challenges from environmental stressors such as temperature fluctuations, deteriorating water quality, and high stocking densities, all of which negatively affect cultured fish's growth and immune competence. Micronutrient supplementation—particularly vitamin C, vitamin E and zinc—has enhanced fish resilience to these stressors.Aims & Methods: This article was prepared using a systematic literature-review approach on the effectiveness of vitamin C, vitamin E and zinc in strengthening the antioxidant and immune systems of fish. A systematic literature search was conducted for articles published within the last ten years in Scopus‐or SINTA‐indexed journals that examined the effects of these micronutrients on the physiological and immunological performance of cultured fish.Results: The evidence indicates that vitamin C at 200–400 mg kg⁻¹ feed, vitamin E at 50-100 mg kg⁻¹ feed and zinc at 30–80 mg kg⁻¹ feed elevate antioxidant-enzyme activity, improve tissue histology, and boost non-specific immune responses. Several species have documented positive outcomes, including Oreochromis niloticus, Clarias batrachus, and Rachycentron canadum. Nevertheless, inter-species variability, interactions with other nutrients, and limited molecular-level studies remain challenges. Further research is required to establish optimal dosages, clarify specific mechanisms of action, and design practical supplementation strategies for sustainable intensive aquaculture.